The Effectiveness of Photobiomudulation therapy (PBMT) in COVID-19 Infection: PBM therapy and COVID19 - Jahani Sherafat, Somayeh; Mokmeli, Soheila; Razaghi, Zahra; Rostami-Nejad, Mohammad; Rezaei Tavirani, Mostafa; Razzaghi, Mohammadreza (Journal of Lasers in Medical Sciences, 2020)
Introduction: Currently, the COVID-19 pandemic is an important health challenge worldwide. Due to the cytokine storm, the mortality rate in acute respiratory distress syndrome (ARDS) is high, but until now no therapy for these patients was approved. The aim of this review was to discuss the possible anti-inflammatory effect of photobiomodulation therapy on ARSD patients and present the potential role of low-level laser therapy in the improvement of respiratory symptoms associated with SARS-COV2. Methods: Studies about photobiomodulation therapy in inflammation and ARSD patients were examined. A primary search with reviewing English-language citations between 2005 and 2020 using the keywords COVID-19, ARDS, cytokine storm, low-level laser therapy, anti-inflammatory, and photobiomodulation was performed. The initial search yielded 818 articles; however, 60 articles were selected and discussed in the present study. Results: The results of the selected studies showed the usefulness of PBMT in the treatment of inflammation and ARSD in patients with COVID-19 infection. This therapy is non-invasive and safe to modulate the immune responses in ARSD patients. Conclusion: PBMT can potentially reduce the viral load and bacterial super-infections in patients with COVID-19 infection and control the inflammatory response. Therefore, the use of PBMT could be an efficient strategy for preventing severe and critical illness in SARS-COV2 infection.